Current perspective for tube feeding in the elderly: from identifying malnutrition to providing of enteral nutrition - Mundi MS (Dove Medical Press, 2018)
Manpreet S Mundi,1 Jayshil Patel,2 Stephen A McClave,3 Ryan T Hurt3–5 1Division of Endocrinology, Diabetes, Metabolism, and Nutrition, Mayo Clinic, Rochester, MN, USA; 2Division of Pulmonary, Critical Care & Sleep Medicine, Medical College of Wisconsin, Milwaukee, WI, USA; 3Division of Gastroenterology, Hepatology and Nutrition, University of Louisville, Louisville, KY, USA; 4Division of General Internal Medicine, Mayo Clinic, Rochester, MN, USA; 5Division of Gastroenterology and Hepatology, Mayo Clinic, Rochester, MN, USA Abstract: With the number of individuals older than 65 years expected to rise significantly over the next few decades, dramatic changes to our society and health care system will need to take place to meet their needs. Age-related changes in muscle mass and body composition along with medical comorbidities including stroke, dementia, and depression place elderly adults at high risk for developing malnutrition and frailty. This loss of function and decline in muscle mass (ie, sarcopenia) can be associated with reduced mobility and ability to perform the task of daily living, placing the elderly at an increased risk for falls, fractures, and subsequent institutionalization, leading to a decline in the quality of life and increased mortality. There are a number of modifiable factors that can mitigate some of the muscle loss elderly experience especially when hospitalized. Due to this, it is paramount for providers to understand the pathophysiology behind malnutrition and sarcopenia, be able to assess risk factors for malnutrition, and provide appropriate nutrition support. The present review describes the pathophysiology of malnutrition, identifies contributing factors to this condition, discusses tools to assess nutritional status, and proposes key strategies for optimizing enteral nutrition therapy for the elderly. Keywords: sarcopenia, home enteral nutrition, elderly, malnutrition, protein